MyIGCSE: STEM IGCSE portal for students / Muhammad Firas Mohd Nazri and Syafillah Abu Hassan - Mohd Nazri, Muhammad Firas; Abu Hassan, Syafillah (Faculty of Computer and Mathematical Sciences, 2023)
The IGCSE (International General Certificate of Secondary Education) examination is an international examination based on STEM (Science, Technology, Engineering, and Mathematics education) that offers various codes of subjects. It is one of the most popular international certifications for secondary school prior to advanced Level (ALevel) or pre-university studies. IGCSE was introduced by Cambridge International Examinations in 1988. Maktab Rendah Sains Mara (MRSM)-IGCSE offers IGCSE program. Every year students both Form 2 and Form 4 are required to take the IGCSE checkpoint and IGCSE examinations. Therefore, it is important for students and teachers to refer to past year examinations as references. However, there is no specific portal for MRSM students taking IGCSE programs. Importantly, this is as an additional reference for students besides those given by the teachers. Therefore, the objective MyIGCSE portal web-based portal for IGCSE portal for MRSM students. The portal provides previous years' papers specifically for MRSM students. The papers are sorted according to the subjects required for each level (Form 2 and Form 4) In addition, students are allowed to download the past year's papers. This portal also includes a discussion board for teachers, parents, and students to further discuss answers or any issues. MyIGCSE portal gives full benefits to students as it allows for discussion among students, downloading past year IGCSE papers including answers, and acknowledges students of new information regarding IGCSE. Therefore, MyIGCSE portal can solve the problem and ease the learning process for students and to support STEM Education in Malaysia.